1
$\begingroup$

I see that this is in the $1^ \infty$ form, so I've taken log to get: $\lim_{x \rightarrow 0} \log( \frac{\tan x}{x})^{\frac{1}{x^2}}$

which is equivalent to

$\lim_{x \rightarrow 0} \frac{\log ( \frac{\tan x}{x} )}{x^2}$

Using L-Hospital's rule for the $0/0$ form, I get:

$\frac {x\sec^2x-\tan x}{2\tan x}$

Using L-Hospital's rule for the $0/0$ form again, I get:

$\frac {2x \sec^2x\tan x}{2\sec^2x}$

Putting the limits, I'm getting this value as $0$ and so taking antilog my result is coming as $e^0=1$

However, the answer is $e^ {1/3}$ which I verified at Wolframalpha.

Can someone please point out my mistake and help me out? thank you

$\endgroup$
  • $\begingroup$ in the first step you forgot an $\ x^3$ term in the denominator $\endgroup$ – Mosk Nov 30 '14 at 1:03
  • $\begingroup$ It seems something went wrong in your first use of L'Hospital's rule. $\endgroup$ – Cameron Buie Nov 30 '14 at 1:04
  • $\begingroup$ The $\frac{1}{x^2}$ is not in the logarithm. You can't use the property $\log{a^x}=x\log a$ $\endgroup$ – UserX Nov 30 '14 at 1:04
2
$\begingroup$

$$\lim_{x\to0}\frac{1}{x^2}\ln\left(\frac{\tan x}{x}\right)=\lim_{x\to0}\frac{1}{x^2}\ln\left(1+\frac{\tan x}{x}-1\right)=$$ $$\lim_{x\to0}\frac{\frac{\tan x}{x}-1}{x^2}=\lim_{x\to0}\frac{\tan x-x}{x^3}=\lim_{x\to0}\frac{x+\frac{x^3}{3}+o(x^3)-x}{x^3}=\frac{1}{3}$$ then: $$\lim_{x\to0}\left(\frac{\tan x}{x}\right)^{\frac{1}{x^2}}=\lim_{x\to0} e^{\frac{1}{x^2}\ln\left(\frac{\tan x}{x}\right)}=e^{\frac{1}{3}}$$

$\endgroup$
  • $\begingroup$ I don't understand your third step, where did the 1 and the ln go? $\endgroup$ – Diya Nov 30 '14 at 10:35
  • 1
    $\begingroup$ $\lim_{t\to 0}\frac{\ln(1+t)}{t}=1$,take $t=\frac{\tan x}{x}-1$ $\endgroup$ – Idele Nov 30 '14 at 13:02
1
$\begingroup$

we will use the two facts $\tan x = x + \frac{1}{3}x^3 + \cdots$ and $e^x = 1 + x + \cdots$ in the form $\lim_{x \to 0}(1+x)^{k/x} = e^k$ to show that the $\lim_{x \to 0}{\frac{\tan x}{x}}^{1/x^2} = e^{1/3}.$

here goes, $\frac{\tan(x)}{x} = 1 + \frac{1}{3}x^2+\cdots$ and now raise this expression to $\frac{1}{x^2}$ to get the claimed result.

$\endgroup$
0
$\begingroup$

Your first use of L'Hopital's rule is wrong. The derivative of $\frac{log ( \frac{tanx}{x} )}{x^2}$ is not $\frac {x \sec^2x-\tan x}{2\tan x}$ but is

$$(\cot x) \left(\frac{\sec^2x}x-\frac{\tan x}{x^2}\right)-\frac{\log \left(\frac{\tan x}x \right)}{x^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.